Reviews - Kaul, Flemming (Journal of Danish Archaeology, 1987)
Reviews: Ian Longworth &John Cherry (eds.): Archaeology in Britain since 1945 (by Flemming Kaul) . Alasdair Whittle: Neolithic Europe: A Survey (by Torsten Madsen). H. Thrane: Lusehej ved Voldto.fte (by Jens Poulsen) . Steen Hvass: Hodde (by Lotte Hedeager). Per Ethelberg: Hjemsted (by Erling Albrectsen) . G. Kossach, K.-E. Behre & P. Schmid (eds.): Landliche Siedlungen (by Steen Hvass).